2018
DOI: 10.3390/molecules23112876
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Characterization of Anthocyanidin Reductase (ANR) from Mangifera indica L.

Abstract: Mango (Mangifera indica L.) is abundant in proanthocyanidins (PAs) that are important for human health and plant response to abiotic stresses. However, the molecular mechanisms involved in PA biosynthesis still need to be elucidated. Anthocyanidin reductase (ANR) catalyzes a key step in PA biosynthesis. In this study, three ANR cDNAs (MiANR1-1,1-2,1-3) were isolated from mango, and expressed in Escherichia coli. In vitro enzyme assay showed MiANR proteins convert cyanidin to their corresponding flavan-3-ols, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…For a better understanding of flowering initiation, differential gene expression analysis among divergent genotypes is expected to provide meaningful insights (Shalom et al, 2014 ). Moreover, previous studies have focused either on the transcriptome (Sharma et al, 2020 ) or the metabolome of mango for flowering or other traits (Tan et al, 2018 , 2020 ; Shivashankara et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For a better understanding of flowering initiation, differential gene expression analysis among divergent genotypes is expected to provide meaningful insights (Shalom et al, 2014 ). Moreover, previous studies have focused either on the transcriptome (Sharma et al, 2020 ) or the metabolome of mango for flowering or other traits (Tan et al, 2018 , 2020 ; Shivashankara et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the enrichment of flavonoid biosynthesis, flavone and flavonol biosynthesis, isoflavonoid biosynthesis, and upstream phenylpropanoid biosynthesis pathways in all samples. The basic metabolic pathways of flavonoids in plants have been elucidated with genes such as CHS, CHI, CYP75A, ANR, FLS and DFR, known to play a key role in the synthesis of bioactive components in medicinal plants [31][32][33][34][35][36][37][38][39] . In this study, the expression of FLS and DFR were upregulated in the leaves and flowers of the small flower group compared to the large flower group, which led to the enhanced accumulation of maohuoside B, lcariside II, Epimedin B, maohuoside A and diphylloside B.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, these marker genes were identified as key genes in the above pathways and were involved in stress resistance. For example, in tobacco, the overexpression of DFR or ANR , which encode crucial regulatory enzymes for flavonoid synthesis, improves the resistance of plants to biotic or abiotic stresses ( Tan et al., 2018 ; Sun et al., 2021 ). The transcription levels of TPS family genes and jasmonate-responsive genes in cotton plants treated with plant-growth-promoting rhizobacteria were higher than those in the untreated control plants and exhibited improved resistance to Spodoptera exigua ( Zebelo et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%